King Richard III (methuen, 1981)
"The Arden Shakespeare is the definitive edition of Shakespeare's work. Justly celebrated for its authoritative scholarship and invaluable commentary, Arden guides you to a richer understanding and appreciation of Shakespeare's plays." -- Back cover.